Peran Lembaga Keuangan Syariah Dalam Meningkatkan Kesejahteraan Karyawan Pada PT. BPRS Al-Wasiyah Medan - Arjuna, Esi; Khaira, Mutia (Business and Investment Review, 2023)
Employee satisfaction is one of the good aspects of a company, with the welfare of employees while working the work process will be better. Because in addition to the place or office that is given when working, living allowances and bonuses, where to live is also an aspect of someone choosing to work in an agency. These employee welfare services are intended to provide a balance in obtaining physical and psychological security for employees and their families as well as creating calm, morale, dedication, discipline, and employee loyalty to the company, so that labor turnover is relatively low. Experts in human resource management have defined the notion of employee welfare in various human resource management literature and books. Employee welfare is complementary remuneration (material and non-material) provided based on policy, aimed at maintaining the physical and mental condition of employees, so that employee work productivity increases. Abstrak Kepuasan karyawan merupakan salah satu aspek dilihatnya baiknya suatu perusahaan, dengan kesejahteraan hidup karyawan selama bekerja proses pekerjaan akan lebih baik. Karena selain tempat atau kantor yang diberikan saat bekerja, tunjangan hidup baik bonus, tempat tinggal juga menjadi aspek seseorang memilih untuk bekerja disebuah instansi tersebut. Pelayanan kesejahteraan karyawan tersebut dimaksudkan untuk memberikan keseimbangan dalam memperoleh keamanan dari segi fisik dan psikis bagi karyawan beserta keluarganya serta menciptakan ketenangan, semangat kerja,dedikasi,disiplin,dan sikap loyal karyawan teerhadap perusahaan, sehingga labour turnover relatif rendah. Pakar ilmu manajemen sumber daya manusia telah mendefinisikan pengertian kesejahteraan karyawan didalam berbagai literatur dan buku-buku manajemen sumberdaya manusia. Kesejahteraan karyawan adalah balas jasa pelengkap (material dan non material) yang diberikan berdasarkan kebijaksanaan,bertujuan mempertahankan kondisi fisik dan mental karyawan, agar produktivitas kerja karyawan meningkat. Kata Kunci :Kesejahteraan Karyawan, Kesejahteraan dalam Al-Quran